1993
DOI: 10.1002/oms.1210281240
|View full text |Cite
|
Sign up to set email alerts
|

Site specificity in the H–D exchange reactions of gas‐phase protonated amino acids with CH3OD

Abstract: H-D exchange reactions of methanol-d, with protonated amino acids were performed in an external-source Fourier transform mass spectrometer. Absolute rate constants were determined for the group which included glycine, alanine, valine, leucine, isoleucine and proline. By comparing reactivities with selected methyl esters, it was found that exchange on the carboxylic acid occurs 3-10 times faster than exchange on the amino group. No simple correlation is observed between the rates of H-D exchange on the acid gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
59
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 35 publications
4
59
1
Order By: Relevance
“…Dookeran and Harrison studied the H/D exchange reactions of 18 naturally occurring amino acids and selected di-and tripeptides with ND 3 , and reported that amino acid [M ϩ H] ϩ ions containing hydroxyl, carboxyl, and amine side chains exchange all labile hydrogen atoms, whereas the side-chain hydrogen atoms of glutamine, asparagine, and histidine [M ϩ H] ϩ ions exchange less readily, and tyrosine and arginine [M ϩ H] ϩ ions do not undergo significant exchange [18]. In a separate study, Lebrilla et al found that the carboxylic acid group of glycine and aliphatic amino acid [M ϩ H] ϩ ions (alanine, valine, leucine, isoleucine, and proline) undergo H/D exchange three to 10 times faster than the N-terminal amino group when reacted with CH 3 OD [19]. Kovačevič et al observed unusual reactivity of histidine [M ϩ H] ϩ ions with CD 3 OD and D 2 O: (1) three equivalent fast exchanges, (2) one nonequivalent fast exchange, and (3) one extremely slow exchange, which they assigned to the protonated amino group, the carboxylic acid group and the distal imidazole nitrogen, respectively [20].…”
mentioning
confidence: 99%
“…Dookeran and Harrison studied the H/D exchange reactions of 18 naturally occurring amino acids and selected di-and tripeptides with ND 3 , and reported that amino acid [M ϩ H] ϩ ions containing hydroxyl, carboxyl, and amine side chains exchange all labile hydrogen atoms, whereas the side-chain hydrogen atoms of glutamine, asparagine, and histidine [M ϩ H] ϩ ions exchange less readily, and tyrosine and arginine [M ϩ H] ϩ ions do not undergo significant exchange [18]. In a separate study, Lebrilla et al found that the carboxylic acid group of glycine and aliphatic amino acid [M ϩ H] ϩ ions (alanine, valine, leucine, isoleucine, and proline) undergo H/D exchange three to 10 times faster than the N-terminal amino group when reacted with CH 3 OD [19]. Kovačevič et al observed unusual reactivity of histidine [M ϩ H] ϩ ions with CD 3 OD and D 2 O: (1) three equivalent fast exchanges, (2) one nonequivalent fast exchange, and (3) one extremely slow exchange, which they assigned to the protonated amino group, the carboxylic acid group and the distal imidazole nitrogen, respectively [20].…”
mentioning
confidence: 99%
“…However, in the gas phase there are many structural parameters apart from the surface availability that affect the HDX rates, as illustrated in a recent HDX study on ion-mobilityselected charge states of bovine ubiquitin [17]. Systematic studies on small peptide systems showed that the difference in proton affinity of the biomolecules and deuterated donor reagent plays a crucial role in the HDX mechanism [7][8][9][10]19]. Beauchamp and coworkers [9] suggested that lower basicity reagents, such as D 2 O and CH 3 OD, proceed via a "relay" mechanism [20] for protonated peptides, while the higher basicity ND 3 reagent gives rise to an "onium" mechanism [21].…”
mentioning
confidence: 99%
“…In contrast, mass spectrometry requires little sample, and with electrospray ionization (ESI) or soft laser desorption/ionization (John Fenn and Kiochi Tanaka 2002 in chemistry), a wide variety of biomolecules and specific complexes can be introduced into a mass spectrometer. A number of methods have been developed to probe the general three-dimensional shapes of biomolecule ions and noncovalent complexes using the techniques of ion mobility [1][2][3][4][5][6][7][8], H/D exchange both in solution [9,10] and the gas phase [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28], and proton-transfer reactivity [29,30].…”
mentioning
confidence: 99%
“…Although gas-phase H/D exchange has been used extensively to characterize peptides and small molecules [11][12][13][14][15][16][17][18][19][20][21], and the structure of some gas-phase proteins [22][23][24], very little work has been done with noncovalent complexes involving biological ions, and this noncovalent work has focused on peptide dimers [25,26] and peptide complexes with metal ions [16,18,21,27] and small molecules [15,28].…”
mentioning
confidence: 99%